Thermal pion condensation: holography meets lattice QCD - Kovensky, Nicolas (2024)
The holographic Witten-Sakai-Sugimoto model is often employed to describe strongly-coupled baryonic and isospin-asymmetric matter, for example in the context of neutron stars. Here we consider the case of vanishing baryon chemical potential, where detailed comparisons to data from lattice QCD are possible. To this end, we extend previous works by including a realistic pion mass and pion condensation into the decompactified limit of the model and evaluate the system for arbitrary isospin chemical potentials and temperatures. After suitably fixing the 3 parameters of the model, we find that the overall phase structure is in excellent agreement with lattice results. This also holds for observables at low temperatures in the strongly coupled regime, while we discover and discuss some discrepancies at large temperatures. Our findings give reassurance for the validity of previous and future applications of this model and highlight the aspects where improvements are needed.